A paradox of three decades of neoliberal economic reforms in Ghana: a tale of economic growth and uneven regional development. Issue 3 (2nd September 2018) - Awanyo, Louis; Attua, Emmanuel Morgan
Abstract : Thirty years of neoliberalization in Ghana is an enigma. On the one hand it is associated with sustained economic growth and decline in the national incidence of poverty, and on the other hand it is characterized by uneven regional development that concentrates growth in historically favored regions and leaves persistently high levels of poverty in certain regions. Informed by primary and secondary research, the paper interprets this enigma as inextricably tied to the reestablishment of incentives and benefits in favor of external capital and particular regional/territorial divisions of labor and capital under neoliberal market reforms. Neoliberalization is portrayed as highlighting capitalism's opposing tendencies of primarily reinforcing the historical concentration of capital and socioeconomic advantage in the Greater Accra and Ashanti Regions, while sustaining the concentration of poverty in the northern regions, and yet to some degree, dispersing capital and socioeconomic benefits to other regions, and reconfiguring broad patterns of uneven regional development.